Advance of income and performance tax business: Evidence for the medians and big Business from Ecuador - Paladines Gallardo , Ariell (2020)
The relationship between corporate taxes and companies’ financial performance has been extensively studied in economic literature. However, special taxes such as the Advance Income Tax (AIT) have limited studies, especially if it is quantitative evidence. This paper estimates the relationship between the distribution of Ecuador’s large and medium-sized companies in the AIR payment and the economic-financial performance. The study uses four measures of business performance; earnings, recruitment, investment and liquidity.  Using a panel of active companies in the 2014-2018 period, the relationship between AIR payment and the economic and financial performance of the companies was estimated. The results suggest that, for the highest levels of the AIR payment distribution, there is a negative correlation with business performance. Furthermore, estimates indicate that the reduction or exemption in this type of tax has a positive and significant relationship with financial performance and not with variables of the real sector of the economy.